A Deep Learning Based Method to Detect Email and SMS Spams - Abdullahi, Abdullahi Abba; Kaya, Mehmet (Ieee, 2021)
Over the last decade, smartphone overuse has made users dependent on digital communication tools such as Email and SMS. The use of e-mail and SMS services, which are generally used for two-way communication, by individuals and organizations as a one-way communication tool for notification, warning, and a reminder has greatly increased. However, these communication media are vulnerable to malicious attacks called spam. In order to detect these spams quickly and accurately, the success of the previous studies with machine learning could not exceed a certain level. In this study, a method is proposed to more accurately identify spam in e-mails and SMS using the deep learning method. The results of the experiments on the real dataset show that the proposed method is superior to the classical machine learning approaches.
International Conference on Decision Aid Sciences and Application (DASA) -- DEC 07-08, 2021 -- ELECTR NETWORK
Keywords: Deep learning; Machine learning; Email and SMS Spam Detection